1997
DOI: 10.1051/jp4:19973150
|View full text |Cite
|
Sign up to set email alerts
|

Ductile Fracture of Pure Copper : An Experimental and Numerical Study

Abstract: Abstract. This paper describes the results of interrupted tensile tests carried out on 99.95% pure copper specimens over a range of stress triaxiality conditions. The tested specimens were sectioned and polished to identify the conditions at which voids nucleate and coalesce before the final fracture takes place. Results show that void nucleation and coalescence both have a very strong dependence on stress triaxiality, but appear to be less sensitive to strain-rate. Based on the combined experimental and numer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…Then another specimen is tested by repeated loading and unloading at different plastic strain to get the change of E for corresponding strain. Seven numbers of independent specimens were also loaded upto 8,12,16,20,25,30, and 40% plastic strains and the tests were interrupted. These specimens were used to study the effect of strain on the void density by micro-structural observation using an optical microscope, SEM and Zeiss software.…”
Section: Tensile Deformation Of Flat Rectangular Specimen Without Anymentioning
confidence: 99%
See 1 more Smart Citation
“…Then another specimen is tested by repeated loading and unloading at different plastic strain to get the change of E for corresponding strain. Seven numbers of independent specimens were also loaded upto 8,12,16,20,25,30, and 40% plastic strains and the tests were interrupted. These specimens were used to study the effect of strain on the void density by micro-structural observation using an optical microscope, SEM and Zeiss software.…”
Section: Tensile Deformation Of Flat Rectangular Specimen Without Anymentioning
confidence: 99%
“…In a study, Milza at al. [12] got that void nucleation and coalescence both have a very strong dependence on stress tri-axiality, but appear to be less sensitive to strain-rate for ductile material like pure copper. Osman [13] observed that due to presence of free graphite and nonspheroidal graphite in ductile cast iron, the fatigue crack initiate and propagates easily and the fatigue strength decreases.…”
Section: Introductionmentioning
confidence: 99%
“…Mirza et al [26] studied the influence of the stress triaxiality using copper specimens; they performed tensile tests stopped before failure in order to, once unloaded, polish them to observe the matrix inside the specimen and identify internal damage. They concluded that the stress triaxility plays a paramount role in how the nucleation-growth-coalescence mechanism develops.…”
Section: Influence Of Stress Triaxiality On Ductile Fracturementioning
confidence: 99%
“…Since its appearance, it has been often used to study fracture in ductile materials and is still a referent model in the field. The model is able to reproduce ductile fracture in many materials [26,62,63], has been compared with other models proving to be very precise [64] and has even been used to study cases of ductile-brittle damage transition [65].…”
Section: Gurson-like Modelsmentioning
confidence: 99%
“…Several ductile damage models have been developed over the years. One of the first works was carried out by Mirza et al [23]. They studied the influence of the stress triaxiality using copper specimens concluding that the strain triaxiality plays a fundamental role in the failure of metals.…”
mentioning
confidence: 99%